Hollow Fibers for Hepatocyte Encapsulation and Transplantation: Studies of Survival and Function in Rats - Michael B. Yang (Cell Transplantation, 1994)
In this study, the feasibility of transplanting hepatocytes using hollow fibers (HF) was investigated. Experiments were carried out in vitro and in vivo to determine the viability and function of hepatocytes encapsulated in four different types of commercially available HF: regenerated cellulose HF (RCHF), polysulfone HF of two different sizes (PSHF-1 and PSHF-2), and polyvinylidine HF (PVDF). Hepatocytes remained viable in all types of HF for at least 1 wk in vitro as measured by light microscopy and their ability to synthesize protein and secrete albumin. However, the levels of protein synthesis and albumin secretion in these cells varied significantly between different HF (RCHF > PSHF-2 > PVDF ã PSHF-1) and appeared to be inversely related to their internal diameters (215, 500, 1000, and 1100 μm for RCHF, PSHF-2, PVDF, and PSHF-1, respectively). While PSHF-2, PVDF, and PSHF-1 did not support long term viability in vivo, hepatocytes in RCHF survived after implantation in the mesentery. After 24 h in vivo, the hepatocytes appeared morphologically intact and exhibited a similar rate of protein synthesis when compared with cells cultured in parallel. The hepatocytes in RCHF also maintained the ability to synthesize protein after 7 days in vivo. These results suggest that HF of appropriate size may be useful for hepatocyte transplantation applications in which prevascularization is not possible.